RANCANG BANGUN SISTEM PAKAR MENDIAGNOSA TINGKAT STRES PADA MAHASISWA SEMESTER AKHIR DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR: Expert System, Stress, Final Student, Certainty Factor. - Harahap, Fitriana (LP2M Universitas Nurdin Hamzah, 2018)
Stress is a reaction that occurs to the physical, psychological, and also behavior. Where stress is in a person is not necessarily the same as the stress experienced by others, due to the factors that affect the level of maturity factor of a person to his environment. If a person responds to stress in a positive direction, then stress will have a positive impact on that person. Conversely, if a person responds to stress toward a negative, it will be bad for the person. With the demands to complete the thesis, final students will basically experience various obstacles that must be undertaken when preparing the thesis. Constraints that arise when preparing a thesis often makes students become desperate and depressed or better known as